Effects of macrophytes and environmental factors on sediment denitrification in a subtropical reservoir. (15th June 2022) - Bu, Hongmei; Fry, Brian; Burford, Michele A.
Abstract: Sediment denitrification plays an important role in nitrogen removal in aquatic systems. However, the importance in nitrogen removal in reservoirs, with a focus on seasonal differences of conditions such as macrophyte beds and environmental factors, is less well understood. This study examined sediment denitrification rate (Dn ), and their potential controlling factors were determined in both macrophyte beds and deeper waters in the subtropical reservoir. The mean Dn in the reservoir annually was 18.0 ± 6.3 (mean ± S.E.) mmol N m −2 d −1, with significant seasonal variation ( p < 0.01), i.e. 43.2 ± 12.8, 6.7 ± 6.3, and 4.0 ± 2.2 mmol N m −2 d −1 in winter, spring and summer respectively. There were no statistical differences in Dn between shallow waters with macrophyte beds and deeper waters without macrophyte beds, although macrophyte beds had higher denitrification rates in summer. The Dn rates were significantly correlated with temperature, conductivity, dissolved oxygen, pH, nitrate-nitrogen concentration (NO3 − -N) ( p < 0.01) and turbidity ( p < 0.05). Linear regression models demonstrated environmental variables explained between 36% and 76% of the variation in Dn . The correlation with NO3 − -N concentrations suggests that it may be a limited factor for Dn . Annual nitrogen removal of the reservoir by a combination of sediment and water denitrification was totally estimated to be 370 t N with an annual removal efficiency of approximately 11%. Nitrogen removal was much higher in winter than other seasons, with about 305 t N removed, accounting for 12% of the total nitrogen inputs. Therefore, denitrification appears to play a minor role throughout much of the year, but in winter months when nitrate accumulates, it may play a more major role. Graphical abstract: Image 1 Highlights: Dn in the reservoir showed significant seasonal variation. Dn was no statistical difference with and without macrophyte beds. NO3 − -N concentrations may be a limited factor for Dn . Denitrification resulted in 12% loss of nitrogen in winter in reservoir ecosystem.